FORMATION OF MORAL CONCEPTS IN PRESCHOOL CHILDREN - Nigmatova Mavjuda Zuvaydulloyevna; Sh. Mirziyoyev (Zeta Repository, 2023)
Moral behaviors in children are essential as they teach them to develop positive traits such as kindness and compassion. In addition, it teaches them to distinguish right from wrong. Also, it helps them develop empathy for others and builds their self-esteem.